Bandgap formation and tuning in gyroid lattice structures: Simulations and experiments - Mohammad Shaaban; Sami El-Borgi; Aravind Krishnamoorthy (Materials & Design)
This study provides a comprehensive investigation of the mechanical bandgap characteristics of gyroid lattice structures. Two methods are used to predict the bandgaps. The first examines wave dispersion in a single unit cell to identify bandgaps through dispersion curves. The second employs harmonic analysis on a finite structure to calculate its steady-state response and plot the frequency response function (FRF). To validate the numerical predictions, PLA matrix and network gyroids samples are manufactured using Fused Deposition Modeling (FDM) and tested for vibration attenuation. The network gyroid demonstrated superior bandgap performance compared to the matrix gyroid, with the broadest bandgap spanning between 6.61 kHz and 7.74 kHz. Parametric studies revealed that the wall thickness, unit cell size, and material properties significantly influence the location and bandwidth of bandgaps, enabling their precise tuning. These findings highlight the potential of the network gyroid structures for vibration-sensitive engineering applications.